U-5: RIGHTS OF STUDENT SPECIALLY WOMEN PROTECTION IN THE PRESPECTIVE OF SEERAH-E-TAYYABAH: طالب علم کے حقوق بالخصوص تحفظ نسواں / طالبات : سیرت طیبہ کی روشنی میں - Abbas, Ghulam; Raza, Tabussam; Ali, Farooq (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
In this article, girls’ students’ rights and women's protection in educational institutions have been described in light of Seerat-un-Nabi according to the principles of research. Allah Almighty has described the process of creation of the universe and its administration/arrangements by using the comprehensive term "Al-Haq". That's why, there is a dire need to seek guidance from Seerat-e-Tayyaba to ensure and to establish peaceful and far-reaching/result-oriented, constant and substantial educational procedures and ethical training for character building. In the light of relevant Ahadith, significant coherent and researched based events examples from Seerat-un-Nabi and from four Guided Caliphs' regimes have been discussed in this article. In accordance with these instructions, practical and prominent events of Seerat-e-Tayyaba have also been explained with argumentive and original systematic sources. The entire discussion is based on thought-provoking and insightful as well as applied and coincidental features for the protection of girls’ students' educational rights and honor and dignity and their ethical training. In this age of ever-increasing importance of social media besides girls' educational rights, their integrity and righteousness can also be ensured, and they can be prepared/trained to face contemporary challenges and to find out the best ever possible and effective solutions.